NON-VERBAL IS A PART COMMUNICATION - Najamuddin Najamuddin (El-Tsaqafah : Jurnal Jurusan PBA, 2016)
Nonverbal communication express meaning or feeling without words. Universal emotions, such as happiness, fear, and sadness, are expressed in a similar nonverbal way throught the world. There are, however, nonverbal differences across cultures that may be a source of confusion for foreigners.Culture does not always determine the messages that our body movements convey. Contexts, personalities, and relationships also influence them. Therefore, no two people in any one society have the same nonverbal behavior. However, like verbal language, nonverbal communication cannot be completely separated from culture